Restoring Motor Neurons in Spinal Cord Injury With Induced Pluripotent Stem Cells - Trawczynski, Matthew; Liu, Gele; David, Brian T.; Fessler, Richard G. (Frontiers in Cellular Neuroscience, 2019)
Spinal cord injury is a devastating neurological disorder that damages motor, sensory, and autonomic pathways. Recent advances in stem cell therapy have allowed for the in vitro generation of motor neurons showing electrophysiological and synaptic activity, expression of canonical motor neuron biomarkers, and the ability to graft into spinal lesions. Clinical translation, especially the transplantation of motor neuron precursors in spinal lesions, has thus far been elusive because of stem cell heterogeneity and protocol variability, as well as a hostile microenvironment such as inflammation and scarring, which yield inconsistent pre-clinical results without a consensus best-practice therapeutic strategy. Induced pluripotent stem cells (iPSCs) in particular have lower ethical and immunogenic concerns than other stem cells, which could make them more clinically applicable. In this review, we focus on the differentiation of iPSCs into neural precursors, motor neuron progenitors, mature motor neurons, and motor neuron subtype fates. Previous reviews have summarized motor neuron development and differentiation, but an up-to-date summary of technological and experimental advances holding promise for bench-to-bedside translation, especially those targeting individual motor neuron subtypes in spinal cord injury, is currently lacking. We discuss biological mechanisms of motor neuron lineage, recent experimental protocols and techniques for motor neuron differentiation from iPSCs, and transplantation of neural precursors and motor neuron lineage cells in spinal cord lesions to restore motor function. We emphasize efficient, clinically safe, and personalized strategies for the application of motor neurons and their subtypes as therapy in spinal lesions.